Trends and clinical profile of leprosy cases in children and adolescents under 15 years old in inland Bahia, Brazil - Martinez, Alessandra Barboza Resende (2025)
Leprosy remains a significant public health challenge in Brazil, and its transmission among children and adolescents under 15 years old is predominantly associated with household contacts. Monitoring the leprosy cases within this specific age group serves as a crucial indicator for disease surveillance and control efforts. Thus, the aim of this study was to describe the trend and clinical profile of leprosy in children and adolescents under 15 years old in inland Bahia, Brazil. This retrospective cross-sectional follow-up study was performed in a specialized reference center in the Paulo Afonso municipality, Bahia. The data were obtained from the records of leprosy patients under 15 years, treated and followed up by the service between 2008 and 2022. The mean new case detection rate of leprosy in children and adolescents at 13.6 (95% CI: 7.9–19.4) cases per 100,000. The highest frequency was in the 10- to 14-year-old age group, comprising 62.1% of cases. Contact screening identified 31.0% of cases, and 12.3% had some disability at diagnosis. Paucibacillary cases (77.6%) were more prevalent than multibacillary, with tuberculoid clinical form (56.9%). The cure rate was 96.4%. The study highlights the need to intensify epidemiological surveillance efforts, including actively searching for cases, particularly among individuals aged 10 to 14 years, who represent the highest proportion of leprosy cases. Targeted interventions and education campaigns tailored to this age group are imperative to enhance awareness, early detection, and access to care, ultimately mitigating the burden of leprosy and preventing long-term sequelae among children and adolescents.